2008
DOI: 10.5301/hip.2008.356
|View full text |Cite
|
Sign up to set email alerts
|

Role of hip arthrodesis in current practice: long term results following conversion to total hip arthroplasty

Abstract: Arthrodesis remains a sensible and safe treatment option maintaining independent mobility without multiple operations or significant bone loss for 20-30 years which subsequently can be successfully converted to an arthroplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 14 publications
2
11
1
Order By: Relevance
“…Richards and Duncan [57] used only self-administered QOL outcome questionnaires in their study, but we think the combination of a surgeonadministered hip-specific score (HHS) measuring hip function, and a patient self-administered health-related QOL survey allows for a more global assessment of patients [43]. Our data confirm that of other studies [29,36,40,49,54,58,65] documenting improved function and QOL after conversion and similar to the improvements after a PTHA ( Table 5). The HHSs achieved by our patients after conversion were similar to those reported in other studies [53,58,62] and, although lower than those for the PTHA for the general population [37,42], they were comparable or better than those obtained in other particular populations such as young patients, patients with high demands, or patients with an important handicap secondary to multivariate hip disorders or polyarticular impairment [43,56].…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…Richards and Duncan [57] used only self-administered QOL outcome questionnaires in their study, but we think the combination of a surgeonadministered hip-specific score (HHS) measuring hip function, and a patient self-administered health-related QOL survey allows for a more global assessment of patients [43]. Our data confirm that of other studies [29,36,40,49,54,58,65] documenting improved function and QOL after conversion and similar to the improvements after a PTHA ( Table 5). The HHSs achieved by our patients after conversion were similar to those reported in other studies [53,58,62] and, although lower than those for the PTHA for the general population [37,42], they were comparable or better than those obtained in other particular populations such as young patients, patients with high demands, or patients with an important handicap secondary to multivariate hip disorders or polyarticular impairment [43,56].…”
Section: Discussionsupporting
confidence: 81%
“…However, samples of patients with fused hips are scarce. Only Joshi et al [36] and Sirikonda et al [65] have reported more patients than in our study (Table 5). We used clinical rating systems with high responsiveness and effect size [17,33,51].…”
Section: Discussioncontrasting
confidence: 49%
See 3 more Smart Citations